PENGEMBANGAN SISTEM INFORMASI DESA BERBASIS WEB PADA KANTOR DESA TUGONDENG - Ramadani, Rina Aulia; Wirawan, Raden; Syam, Nurwahid (CV. LAJAGOE PUSTAKA, 2025)
This study aims to: (1) know the process of developing a Web-based Information System at the Tugondeng Village Office. (2) know the process of using the Web Information System at the Tugondeng Village Office. This research uses qualitative methods using an R&D or Research and Development approach to develop a Village Information System at the Tugondeng Village Office. This method has 6 stages of preparation including: (1) identifying potential problems, (2) research and data collection, (3) design, (4) design validation tests, (5) product validation and finally (6). This research uses data collection techniques, namely, observation, interviews, literature studies, questionnaires / questionnaires, documentation. The results of the study, using a Database Management System (DBMS) consisting of use cases, class diagrams, activity diagrams, and sequence diagrams. This system uses a MySQL database using Research and Development and uses PHP, CSS, and HTML programming languages, showing the results that the implementation of a website-based village information system effectively facilitates access to information for residents, such as village budget data, population data, activity agendas, beneficiary data and public services. The web-based village information system in Tugondeng village gave a response result with a value of 84.8%, which means that it strongly agrees with the existence of a web-based village information system at the Tugondeng village office.